MODEL IMPLEMENTASI BANTUAN HUKUM ORANG MISKIN BAGI PENCARI KEADILAN (Lex Jurnalica, 2019)
AbstractThe principle of the presumption of innocence is the principle of article 39 Magna Charta-1215, for the sake of the realization of an honest, fair and impartial judicial process. In addition to the presumption of innocence rights, a suspect and defendant in modern procedural law is to obtain legal assistance, where legal assistance has an important position in the justice system, especially legal assistance for suspects and defendants who are classified as people or groups of poor people, where legal assistance is provided free of charge. In fact, there were many irregularities in the implementation of the provision of legal assistance. therefore it is necessary to know about the implementation of legal assistance for people or groups of poor people for justice seekers and processes and inhibiting factors for their implementation. This legal research uses a form of descriptive normative legal research. The conclusion obtained from this study is that the implementation of legal assistance for citizens seeking justice in criminal cases has not been implemented properly. Deviations can still be found at the stage of examination of suspects at the level of investigation at the police station and at the stage of the defendant's examination at the district court. Keywords:Legal aid, poor people, justice seekers. AbstrakAsas praduga tak bersalah merupakan prinsip dari pasal 39 Magna Charta-1215, demi terwujudnya proses peradilan yang jujur, adil dan tidak memihak. Selain hakperlakuan asas praduga tak bersalah, seorang Tersangka dan terdakwadalam hukum acara modern adalahuntuk memperoleh bantuan hukum, dimana bantuan hukum memiliki kedudukan yang cukup penting dalam sistem peradilan,khususnya bantuan hukum bagi tersangka dan terdakwa yang tergolong sebagai orang atau kelompok orang miskin, dimana bantuan hukum diberikan secara cuma-cuma. Faktanya, ditemukan banyak penyimpangan-penyimpangan dalam pelaksanaan pemberian bantuan hukum. oleh sebab itu perlu diketahui mengenai implementasi bantuan hukum bagi orang atau kelompok orang miskin bagi pencari keadilan dan proses serta faktor-faktor penghambat pelaksanaannya. Penelitian hukum ini menggunakan bentuk penelitian hukum normatif yang bersifat deskriptif. Kesimpulan yang diperoleh dari penelitian ini adalah bahwa implementasi bantuan hukum bagi warganegara pencari keadilan dalam perkara pidana belum dapat diimplementasikan dengan baik. Penyimpangan-penyimpangan masih dapat ditemukan pada tahap pemeriksaan tersangka ditingkat penyidikan di polres dan pada tahap pemeriksaan terdakwa di sidang pengadilan negeri. Kata kunci:Bantuan hukum, orang miskin, pencari keadilan